Paleopathological changes in the Carpathian Basin in the 10th and 11th centuries - Marcsik, Antónia; Fóthi, Erzsébet; Hegyi, Andrea (Acta Biologica Szegediensis, 2002)
The existence of skeletal materials and accompanying archaeological subsistence data recording the shift from nomadic animal husbandary to sedentary agriculture during the 10th and 11th centuries in the Carpathian Basin offers the opportunity to document shifts in the frequencies in various disease categories. On the basis of the data from the literature of the paleopathological cases, skeletal samples representing 714 tenth and 970 eleventh century individuals are grouped for indications of environmental stress: specific disease stress (porotic hyperostosis), infections, traumatic lesions, degenerative arthritis and genetic and/or environment indicators (developmental anomalies). The frequency of lesions in the samples should not be extrapolated to the larger population, but may only be used as an indicator of a trend in the appearance of the diseases. The results suggest some significant shifts for some disease and little change for other diseases during the transition from a nomadic to a more sedentary way of life.